Do Acquisitions and Mergers Improve Corporate Performance: Evidence from Chinese Listed Companies - CHEN, Yuhong (2016)
Abstract During the last decade, Chinese M&A activities have experienced a dramatic upward trend. Increasing scholars investigate Chinese M&A and test the influence of Chinese acquisitions and mergers on firms’ post-merger performance. However, their studies about the impact of M&A activities on firms’ post-merger performance are still mixed. This paper includes sample data of 743 Chinese M&A deals that took place during the period of 2000 to 2010. Industry adjusted operating cash flows on assets, operating margin, ROA and ROE were used as measures to capture post-merger performance. We test the influence of M&A activities on post-merger performance and also examine the determinants that might influence the post-merger performance. Cross-sectional regression models are used to capture the abnormal industry adjusted returns and sample OLS regression models are used to test the relationship between the post-merger performance and its determinant factors. Empirical results shows that merged firms have improve their post-merger performance significant for the first three years after acquisitions, however, for the long-term, M&A does not improve merged firms’ performance. Besides, regression results reports that mergers within the same industry will improve the post-merger performance for both short and long term; target profitability would significantly improve post-merger performance for the short-term; high level of leverage will depress the post-merger performance for both short and long term; relative size has significant negative influence on post-merger performance for the short-term and this influence becomes positive for the long-run.